The distributional effects of personal income tax expenditure - Silvia Avram (University of Essex, Institute for Social and Economic Research (ISER), 2014)
Using EUROMOD, this study investigates the size and distributional effects of tax allowances and tax credits in 6 European countries. It also examines whether instrument design matters in shaping the redistributive effect, paying attention to both categorical and explicit income targeting .With few exceptions the impact of tax allowances and tax credits on inequality is small. Tax credits are generally more progressive than tax allowances. The design of the allowances/credits appears to be less important than the characteristics of the population they are targeting and/or other features of the income tax system in determining the redistributive effect. Consequently, tax concessions appear ill-suited to target resources towards households in the bottom part of the income distribution.
Keywords: D31; H24; I38; 330; tax expenditure; redistribution; income tax; microsimulation